Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.1039/d3ta01471a
|View full text |Cite
|
Sign up to set email alerts
|

Zinc bromide: a general mediator for the ionothermal synthesis of microporous polymers via cyclotrimerization reactions

Abstract: Conjugated microporous polymers (CMPs) are porous organic materials that display (semi)conducting behavior due to their highly π-conjugated structures, making them promising next-generation materials for applications requiring both electrical conductivity and...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 43 publications
0
0
0
Order By: Relevance
“…Cyclotrimerization usually requires heating of molten salts at temperatures above 300 °C to catalyze polymerization reactions. 73–75 In 2018, Baek et al 75 first reported that phosphorus pentoxide (P 2 O 5 ) catalyzes the direct condensation of aromatic amides to form covalent triazine-based frameworks (CTFs) (Fig. 8a).…”
Section: Synthetic Reactions and Methods Of Cmpsmentioning
confidence: 99%
“…Cyclotrimerization usually requires heating of molten salts at temperatures above 300 °C to catalyze polymerization reactions. 73–75 In 2018, Baek et al 75 first reported that phosphorus pentoxide (P 2 O 5 ) catalyzes the direct condensation of aromatic amides to form covalent triazine-based frameworks (CTFs) (Fig. 8a).…”
Section: Synthetic Reactions and Methods Of Cmpsmentioning
confidence: 99%